The Dynamics of Divorce in Palu City and the Role of the Religious Court in Prevention Efforts in Palu City - Meilany; Susi Susilawati; M. Ayyub Mubarrak (www.amertainstitute.com, 2025)
This study investigates the rising trend of divorce in Palu City and evaluates the role of the Religious Court in preventing marital dissolution through mediation and legal interventions. Divorce, although permissible as a last resort in Islamic law, has become increasingly prevalent, reflecting complex socio-economic and psychological dynamics within households. Using a juridical-empirical qualitative approach, this research analyzes primary data obtained from interviews and observations with divorced parties, alongside secondary data from case files of Cerai Gugat and Cerai Talak registered in the Palu Religious Court from 2022 to 2024. The findings reveal that dominant factors contributing to divorce include infidelity, economic instability, poor communication, domestic violence, loss of marital harmony, and conflicting values. An increasing number of divorces among young couples is also observed, driven by emotional immaturity and socio-economic pressures. Although the Religious Court implements mandatory mediation under the Supreme Court Regulation on mediation procedures, its effectiveness remains limited due to low legal awareness, heightened emotional tension, and external family interference. This study highlights that divorce is not solely a legal matter but also a multidimensional social phenomenon. The research contributes to the development of Islamic family law and provides important insights for policymakers to strengthen preventive measures through legal education, improved mediation quality, and community empowerment.